Ascorbic Acid, Inflammatory Cytokines (IL-1β/TNF-α/IFN-γ), or Their Combination's Effect on Stemness, Proliferation, and Differentiation of Gingival Mesenchymal Stem/Progenitor Cells - Karim M. Fawzy El-Sayed; Nhung Nguyen; Christof E. Dörfer (Hindawi Limited, 2020)
Objective. Ascorbic acid (AA) and controlled inflammatory stimuli are postulated to possess the ability to independently exert positive effects on a variety of proliferative, pluripotency, and differentiation attributes of gingival mesenchymal stem/progenitor cells (G-MSCs). The current study's objective was to explore and compare for the first time the impact of the major inflammatory cytokines (IL-1β/TNF-α/IFN-γ), AA, or their combination on multipotency/pluripotency, proliferative, and differentiation characteristics of G-MSCs. Design. Human G-MSCs (n=5) were isolated and cultured in basic medium (control group), in basic medium with major inflammatory cytokines; 1 ng/ml IL-1β, 10 ng/ml TNF-α, and 100 ng/ml IFN-γ (inflammatory group), in basic medium with 250 μmol/l AA (AA group) and in inflammatory medium supplemented by AA (inflammatory/AA group). All media were renewed three times per week. In stimulated G-MSCs intracellular β-catenin at 1 hour, pluripotency gene expression at 1, 3, and 5 days, as well as colony-forming units (CFUs) ability and cellular proliferation over 14 days were examined. Following a five-days stimulation in the designated groups, multilineage differentiation was assessed via qualitative and quantitative histochemistry as well as mRNA expression. Results. β-Catenin significantly decreased intracellularly in all experimental groups (p=0.002, Friedman). AA group exhibited significantly higher cellular counts on days 3, 6, 7, and 13 (p<0.05) and the highest CFUs at 14 days [median-CFUs (Q25/Q75); 40 (15/50), p=0.043]. Significantly higher Nanog expression was noted in AA group [median gene-copies/PGK1 (Q25/Q75); 0.0006 (0.0002/0.0007), p<0.01, Wilcoxon-signed-rank]. Significant multilineage differentiation abilities, especially into osteogenic and chondrogenic directions, were further evident in the AA group. Conclusions. AA stimulation enhances G-MSCs' stemness, proliferation, and differentiation properties, effects which are associated with a Wnt/β-catenin signaling pathway activation. Apart from initially boosting cellular metabolism as well as Sox2 and Oct4A pluripotency marker expression, inflammation appeared to attenuate these AA-induced positive effects. Current results reveal that for AA to exert its beneficial effects on G-MSCs' cellular attributes, it requires to act in an inflammation-free microenvironment.